Intended and non-intended kinematic effects of atlanto-axial rotational high-velocity, low-amplitude techniques. Issue 2 (February 2015) - Cattrysse, Erik; Gianola, Silvia; Provyn, Steven; Van Roy, Peter
Abstract Introduction The study of neck kinematics during high-velocity, low-amplitude manipulations of the atlanto-axial segment is essential to understanding cervical motion mechanisms and their impact and possible risk for soft-tissue injuries during treatment of spine disorders. Methods Twenty fresh-frozen specimens were tested during manual application of an axial rotation technique. Findings The kinematics indicate the thrust induced motion components of approximately 1° at the treated segment around all three axes of the local embedded reference frame. Moreover, an equal amount of axial rotation motion took place at the adjacent atlanto-occipital joint. Interpretation Overall atlanto-axial motion remained below the level of slow regional mobilization of the cervical spine. These findings can be correlated to literature data concerning the limited increase in vertebral artery strain during high-velocity, low-amplitude manipulation.